Influence of remaining oxide on the adhesion strength of supersonic particle deposition TiO2 coatings on annealed stainless steel - Omar, Nooririnah; Yusuf, Yusliza; Sundi, Syahrul Azwan; Abu Bakar, Ilyani Akmar; Abd Rahim, Toibah; Fabiani, Verry Andre; Yamada, Motohiro (MDPI AG, 2023)
The cold spray or Supersonic Particle Deposition technique has great potential for producing ceramic nanostructured coatings. This technique operates at a processing temperature that is low enough to preserve the initial feedstock materials’ microstructure. Nevertheless, depositing ceramic powders using a cold spray can be challenging because of the materials’ brittle nature. The interaction between substrate and particles is significantly influenced by substrate attributes, including hardness, material nature, degree of oxidation and temperature. In this study, the effect of the substrate’s remaining oxide composition on the adhesion strength of an agglomerated nano-TiO2 coating was investigated. The results showed that the coating adhesion strength increased for hard materials such as stainless steel and pure chromium as the annealed substrate temperature also increased from room temperature to 700 °C, indicating thicker oxide on the substrate surface. TiO2 particles mainly bond with SUS304 substrates through oxide bonding, which results from a chemical reaction involving TiO2-OH−. Chromium oxide (Cr2O3) is thermodynamically preferred in SUS304 and provides the OH− component required for the reaction. SUS304 shows a thermodynamic preference for chromium oxide (Cr2O3), and this enables Cr2O3 to provide the necessary OH− component for the reaction.